Is self-compassion associated with lower psychological distress in people with long COVID? Results from a cross-sectional survey - Luca Bodini; Chiara Bonetto; Morena Colombi; Nila Barbieri; Tine Van Bortel; Antonio Lasalvia (Cogent Psychology)
Long COVID affects approximately 10–20% of COVID-19 patients and has a devastating impact on their quality of life and mental health. This study aimed to evaluate symptoms of psychological distress in people with long COVID and explore whether high levels of self-compassion are associated with low levels of psychological distress. An online cross-sectional survey of people with Long COVID was conducted. In total, 332 respondents participated in the survey. All dimensions of self-compassion were found to be significantly associated with depression, anxiety, and perceived stress, independent of symptom severity. Specifically, self-kindness, common humanity, and mindfulness were strongly negatively associated with distress, whereas self-judgment, isolation, and over-identification were strongly and positively associated with distress. Self-compassion seems to play a role in explaining levels of psychological distress in people with long COVID symptoms. The centrality of self-compassion may lead to the development of effective interventions to help patients with long COVID reduce self-judgmental and self-critical tendencies and improve their psychological well-being.